Estudio de factibilidad para la creación de un centro de desarrollo infantil para niños y niñas del cantón San Jacinto de Buena Fe, año 2015 - Zapata Montece, Patricia Mabell (2015)
The present research work aims to carry out the feasibility study for the creation of a Child Development Center for children of the canton San Jacinto of Buena Fe, which will be located in the sector “La Pradera”, August seven streets and first Eastern. The following studies were conducted to determine the feasibility of the project: Market study; which allowed us to identify the dissatisfaction of 6469 families of the town, in relation to the services provided by the Child Development Centres, for children between one and five years of age. Where the commercial strategy, required to determine as objective, the need to capture the average of forty children for the first year and for the following years, provide for an increase in the number of children 30%. Technical study; It states that the best location for the 'Gift of God' Child Development Center in canton Buena Fe, would be determined in the sector “La Pradera”; your infrastructure must have necessary facilities for the performance of the different areas, such as: care and teaching, recreational, rest or wedge, management, nursing, cellar, kitchen, lounge, bathroom general and baths just for kids, with capacity of 60 children. Likewise, the need to work in different areas such as human resource: director general, Secretariat, Advisory accountant. Operational staff such as: child psychologist, paediatrician, two pre-kindergarten teachers and an Assistant; will also be necessary as support staff: Cook, chauffeur and cleaning, which will lend its services according to the requirements of the centre. In addition, provides necessary to use advertising strategies as: posters that promote and encourage the use of the services provided by the Centre, such as: stimulation of the creative development of children, balanced power….